Characterization of the antibody response to SARS‐CoV‐2 in a mildly affected pediatric population. Issue 2 (21st February 2022) - Kopanja, Sonja; Gattinger, Pia; Schmidthaler, Klara; Sieber, Justyna; Niepodziana, Katarzyna; Schlederer, Thomas; Weseslindtner, Lukas; Stiasny, Karin; Götzinger, Florian; Pickl, Winfried F.; Frischer, Thomas; Valenta, Rudolf; et al.
Abstract: Background: While children usually experience a mild course of COVID‐19, and a severe disease is more common in adults, the features, specificities, and functionality of the SARS‐CoV‐2‐specific antibody response in the pediatric population are of interest. Methods: We performed a detailed analysis of IgG antibodies specific for SARS‐CoV‐2‐derived antigens S and RBD by ELISA in 26 SARS‐CoV‐2 seropositive schoolchildren with mild or asymptomatic disease course, and in an equally sized, age‐ and gender‐matched control group. Furthermore, a detailed mapping of IgG reactivity to a panel of microarrayed SARS‐CoV‐2 proteins and S‐derived peptides was performed by microarray technology. The capacity of the antibody response to block RBD‐ACE2 binding and virus neutralization were assessed. Results were compared with those obtained in an adult COVID‐19 convalescent population. Results: After mild COVID‐19, anti‐S and RBD‐specific IgG antibodies were developed by 100% and 84.6% of pediatric subjects, respectively. No difference was observed in regards to symptoms and gender. Mounted antibodies recognized conformational epitopes of the spike protein and were capable to neutralize the virus up to a titer of ≥80 and to inhibit the ACE2‐RBD interaction by up to 65%. SARS‐CoV‐2‐specific IgG responses in children were comparable to mildly affected adult patients. Conclusion: SARS‐CoV‐2 asymptomatic and mildly affected pediatric patients develop a SARS‐CoV‐2‐specific antibody response, which is comparable regarding antigen, epitope recognition, and the ability to inhibit the RBD‐ACE2 interaction to that observed in adult patients after mild COVID‐19.